1990
DOI: 10.1007/bf00318638
|View full text |Cite
|
Sign up to set email alerts
|

Cellular composition and steroidogenic capacity of the ovary of Macrotus californicus (Chiroptera: Phyllostomatidae) during and after delayed embryonic development

Abstract: In the leaf-nosed bat, Macrotus californicus, a 4.5-month period of delayed early embryogenesis (October-March) precedes a 3.5-month period of normal embryogenesis (March-June). This prolonged gestation provides a unique opportunity to correlate ovarian changes with the events following implantation. The present study investigated luteal cell development and follicular biology during gestation. Circulating progesterone (P) levels following implantation were unchanged before transition to normal development, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…This study also supports a similar finding in another bat species, Macrotus (Crichton et al, 1990) in which low enzyme activity in multilaminar follicles in the ovaries was noticed during delayed embryonic development. The present study supports these findings and provides indirect evidence that the low enzyme activity required for follicular survival during the delay period was found in the ovary, but that this activity was not enough for ovulation leading to prolonged survival of the Graafian follicle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also supports a similar finding in another bat species, Macrotus (Crichton et al, 1990) in which low enzyme activity in multilaminar follicles in the ovaries was noticed during delayed embryonic development. The present study supports these findings and provides indirect evidence that the low enzyme activity required for follicular survival during the delay period was found in the ovary, but that this activity was not enough for ovulation leading to prolonged survival of the Graafian follicle.…”
Section: Discussionsupporting
confidence: 92%
“…While several authors have reviewed the progress of research on reproduction from time to time, detailed studies on ovarian cycle and steriodogenesis are very few (Oxberry, 1979;Racey, 1982;Heideman, 1989;Singh & Krishna, 1997;Martin & Bernard, 2000). The cellular location and relative activities of total phospholipids and neutral lipids, substrates for sex steroids and steroidogenesis, enzymes 3β-HSD, and glucose-6-phosphates (G-6-PD) are described in the ovary of bats Tadarida (Jerrett, 1979); Taphozous (Jaroli & Lall, 1987); Rinolaphus eurale (Tsvetkov & Takeva, 1988); and Macrotus (Crichton et al, 1990). No such information is available on any tropical bat, particularly in relation to the unique reproductive features, which are prolonged survival of the Graafian follicle and delayed ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the bat species showing delayed embryonic development in which serum progesterone levels have been investigated also showed low levels of serum progesterone during the period of delayed embryonic development as compared to the period of normal embryogenesis (Krishna 1999). M. californicus showed low levels of plasma progesterone during the period of delayed development, and its level increased significantly on resumption of normal embryonic development (Crichton et al 1990). The studies on Miniopterus schrebersii showed low circulating progesterone level during delayed implantation (van der Merwe & van Aarde 1989, Bernard et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructure of these three stages suggest that, before implantation cells contain polymorphic profiles of AER, mitochondria and lipid droplets after implantation cells are highly active, and contained numerous steroidogenic organelles (Agranular endoplasmic reticulum, mitochondria and lipid droplets) (Uchida et al, 1984), Miniopterus sp (Crichton et al, 1989;Bernard and Bojarki, 1994), Macrotus californicus (Crichton et al, 1990) and Hipposideros lankadiva (Seraphim, 2004), during pregnancy.…”
Section: Iii) Limb Bud Stagementioning
confidence: 99%
“…By contrast, many studies have appeared describing the fine structure of corpus luteum in other mammals including rabbit (Blanchette, 1966), pig (Cavazos et al ., 1969;Belt et al, 1970), cow (Priedkalns and Weber, 1968), and few bat species, Miniopterus schreibersii fuliginosus (Uchida et al, 1984), Miniopterus sp (Crichton et al, 1989;Bernard and Bojarki, 1994), Macrotus californicus (Crichton et al, 1990) and Hipposideros lankadiva (Seraphim, 2004),Taphozous longimanus (Nerkar and Gadegone 2007)during pregnancy. These studies have described the luteal cells as possessing abundant agranular endoplasmic reticulum mitochondria with tubular cristae osmiophilic lipid droplets, and a well developed Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%